Rapid self-assembly of complex biomolecular architectures during mussel byssus biofabrication - Tobias Priemel (Nature Portfolio, 2017)
Mussels attach to rocks using a byssus, which possesses unique properties of adhesion, toughness and self-healing. Here, the authors explore the fabrication process of mussel byssus demonstrating the self-assembly of specific proteins into multi-scale organized structures using artificially induced byssus threads.